(untitled) (Revista Paradigma, 2023)
This article aims to provide a framework for the construction of a basis for proposing collective guardianships regarding benefits in the field of social security in its diffuse aspect. To this end, the Brazilian experience has indicated that the demands of social security law have been predominantly individual, despite their meta-individual or diffuse nature. It is in this sense that, in the formalized article, we intend to demonstrate that social risks in contemporary times are increasingly complex, as well as the fluidity of the social contingencies covered. In this step, it is clear that social security law must develop a new exposition, incorporating techniques from diffuse and collective rights, in order to produce more uniform and coherent decisions. The research is based on a methodology focused on literature review. In the development of the work, therefore, the hypothetical-deductive methodology will be present and, with it, the survey of conjectures in areas of democratic demarcation. In conclusion, the aim is to demonstrate that Social Security Law is among the branches of Diffuse Law, demonstrating premises for the theorization of collective social security protection.